The work and health process in the sugarcane agroindustry in Franca, Brazil - de Souza Lourenco, Edvania Angela [UNESP]; Bertani, Iris Fenner [UNESP] (Sage Publications Ltd, 2011)
This study aimed to discuss the interrelation between social determinants and the health conditions of workers in the sugarcane agroindustry in the region of Franca, in the countryside of São Paulo State, Brazil, from 2005 to 2006, considering the present socio-economic, historical, political and cultural conditions.
Keywords: social environment; social justice; social work; workers' health